COMPLEX TREATMENT OF COGNITIVE DISORDERS IN PATIENTS WITH MYASTIA (Medical science of Uzbekistan, 2023)
According to the World Health Organization, the prevalence of myasthenia gravis is 17.5–20.3 per 100,000 people. In the world, the indicator increases by 5-10% every year. The first symptoms of myasthenia gravis are skeletal muscle fatigue and weakness during the day with high load, which tends to decrease at rest. Eye muscles are primarily damaged in 2/3 of patients, then skeletal muscles and bulbar muscles are added to the process. Generalizing weakness is observed in 85% of patients. The disease develops rapidly, and spontaneous remission is observed in rare cases. In adults, thyroid gland anomaly is observed in 90% of patients with myasthenia gravis, approximately 70% of them are hyperplasia of the thyroid gland, and 10-20% are thymoma.